Neuromyths in Education: Prevalence Among South Indian School Teachers - Jeyavel, Sundaramoorthy; Pandey, Vijyendra; Rajkumar, Eslavath; Lakshmana, Govindappa (Frontiers in Education, 2022)
This study aimed to find out the existence of neuromyths among school teachers in the South Indian states. An online survey was carried out to assess the school teachers’ general understanding of the brain and their belief on selected seven neuromyths statements. A total of 503 high school and higher secondary school teachers from South India participated in this study. On average, 65.5% of teachers have shown their belief toward more than two of the neuromyths; 84% of the participants have believed the learning style myths. This points out the difficulty of teachers in distinguishing factual information from non-scientific facts or myths. Therefore, there is an important need for involving interdisciplinary conversation that can reduce misunderstandings among teachers in the future.